Analisis Penerapan Sistem Pengeluaran Kas dan Pelaporan Kinerja pada Badan Penanggulangan Bencana Daerah (BPBD) di Kabupaten Pidie Jaya - Ridwan Ibrahim; Adnan Saadi; Azmi Azmi (SI-MEN, 2014)
The type of this research that used in this study is qualitative research with a descriptive approach. This study uses the unit of analysis BPBDs in Pidie Jaya district. The type of data used is secondary data. Data collection techniques used were observation, interviews, and documentation. The purpose of this study is to investigate, analyze how the application of the system of cash expenditure on BPBDs in Pidie Jaya district based on the Regulation of the Minister of Home Affairs Number 13 Year 2006 on Guidelines for Financial Management and reporting performance on BPBDs in Pidie Jaya district based on the Rule Minister of State for Administrative Reform and Bureaucratic Reform No. 29 of 2010 on Guidelines for Preparation and Determination of Performance Accountability of Government Performance Reporting.The results of this study indicate that (1) the application of the system of cash expenditure on BPBDs in Pidie Jaya district has been under Permendagri No. 13 of 2006 on Regional Financial Management Guidelines. (2) Performance Reporting BPBDs in Pidie Jaya district have also been made in accordance with the Regulation of the Minister of State for Administrative Reform and Bureaucratic Reform No. 29 of 2010 on Guidelines for Preparation and Determination of Performance Accountability of Government Performance Reporting